Analisis Konflik Dalam Kericuhan Muspimnas PMII Di Tulungagung Dengan Pendeketan Teori Lewis A. Coser - Mahfiroh, Refi Anita; Yanti, Manda Rosa; Sholehah, Homilatus; Zuhro, Aniq Qotuz (CV. ITTC INDONESIA, 2022)
This research aims to explore the factors that trigger conflict in the MUSPIMNAS PMII riots in Tulungagung, including differences in interests, competition, and social interdependence among the involved groups. In this study, the approach of Lewis A. Coser's conflict theory is utilized to analyze the dynamics of conflict occurring in the MUSPIMNAS PMII riots in Tulungagung. This theory depicts conflict as a struggle between individuals or groups with conflicting interests, and Coser also identifies conflict as a social mechanism that plays a role in social change. The research methodology employed in this study involves the analysis of secondary data. Secondary data is obtained from mass media reports, official documents, and relevant literature. It is expected that the analysis results of this research will provide a deeper understanding of the dynamics of conflict in the MUSPIMNAS PMII riots in Tulungagung, as well as the social and psychological implications that arise as a result of the conflict. Additionally, this study can serve as a theoretical foundation for further research on social conflict and social change within the context of student organizations.